Towards the virtualization of university teaching: A methodological change based on three scenarios - Martínez Robledo, Mª Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Covid-19 pandemic has caused a forced change in university teaching, both methodologically and practically. The University of Granada has created a triple model based on three different scenarios: virtual learning (e-learning), blended learning (b-learning) and face-to-face learning. The objectives that we intend to achieve consist of presenting, analysing and disseminating this pedagogical model created to face future challenges that may arise. For the analysis process, the classroom experience and the results obtained during the three academic years in which this new model has been implemented in one or more of its scenarios will be evaluated.